Scientific research dilemma in contemporary Muslim world - Waleed, Fekry Faris (International Institute for Muslim Unity, International Islamic University Malaysia, 2014)
Islam is a religion that embraces science and knowledge ever since it was revealed more than fifteen hundred centuries ago. Muslim scientists in golden era of middle centuries who were first to develop scientific research methodology paved the way for the advancement of mathematics, science and medicine to the rest of world. However, such situation has been reversed and no major discovery or scientific contribution has been delivered to the world for the past six centuries. The disengagement of Muslim world from acquiring the science and technology frontiers and the process of creating new knowledge despite having more than a billion Muslims together with huge natural and material resources is a worrying and frustrating situation that worth analysis and immediate intervention. In this article the challenges that are facing the scientific research in the contemporary Muslim world and analyze the root causes for the lack of accomplishments in science and technology were be discussed. This article also put forward some recommendations to improve the scientific stands of the Muslim world in the international context.